2015
DOI: 10.1556/1886.2015.00042
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-4 dependent small intestinal immune responses following murine Arcobacter butzleri infection

Abstract: Sporadic cases of gastroenteritis have been attributed to Arcobacter butzleri infection, but information about the underlying immunopathological mechanisms is scarce. We have recently shown that experimental A. butzleri infection induces intestinal, extraintestinal and systemic immune responses in gnotobiotic IL-10–/– mice. The aim of the present study was to investigate the immunopathological role of Toll-like Receptor-4, the receptor for lipopolysaccharide and lipooligosaccharide of Gram-negative bacteria, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Notably, before our previous reports on A . butzleri infected gnotobiotic IL-10 -/- mice [ 13 16 ], only one single in vivo study in mice had been published showing that the adherent properties of initially low-adherent A . butzleri strains were enhanced upon serial intraperitoneal passages [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, before our previous reports on A . butzleri infected gnotobiotic IL-10 -/- mice [ 13 16 ], only one single in vivo study in mice had been published showing that the adherent properties of initially low-adherent A . butzleri strains were enhanced upon serial intraperitoneal passages [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…butzleri infection studies, however, clearly revealed that despite absence of overt gross disease, distinct infection-induced intestinal, extra-intestinal and even systemic sequelae could be observed in an A . butzleri strain dependent manner [ 13 16 ]. These results indicate that gnotobiotic IL-10 -/- mice might serve as infection model to investigate Arcobacter -host interactions to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In situ immunohistochemical analysis of ileal and colonic paraffin sections was performed as previously described ( 25 28 ). Primary antibodies against cleaved caspase-3 (Asp175, Cell Signaling, Beverly, MA, USA, 1:200), Ki67 (TEC3, Dako, Glostrup, Denmark, 1:100), CD3 (#N1580, Dako, 1:10), Foxp3 (FJK-16s, eBioscience, San Diego, CA, USA, 1:100), B220 (eBioscience, 1:200), and F4/80 (# 14-4801, clone BM8, eBioscience, 1:50) were used.…”
Section: Methodsmentioning
confidence: 99%